Anti-Photoaging and Anti-Inflammatory Effects of Ginsenoside Rk3 During Exposure to UV Irradiation - Wan, Shichao; Liu, Yannan; Shi, Jingjing; Fan, Daidi; Li, Binglin (Frontiers in Pharmacology, 2021)
Ginseng is a widely cultivated perennial plant in China and Korea. Ginsenoside Rk3 is one of the major active components of ginseng and is a promising candidate to regulate skin pigments and exert antiphotoaging effects on skin physiology. Ginsenoside Rk3 was mixed into a cream (G-Rk3 cream) and smeared on the skin of mice. Then, the mice were exposed to UVA (340 nm and 40 W) and UVB (313 nm and 40 W) radiation. Special attention was given to the antiphotoaging and anti-inflammatory effects of ginsenoside Rk3 on mouse skin. Macroscopic evaluation indicated that the mouse dorsal skin looked smooth and plump even under UV irradiation for 12 weeks. Pathological analysis indicated that there was no obvious photoaging or inflammation in the mouse skin that was treated with G-Rk3 cream. More healthy, intact and neat collagen fibers were observed in mice treated with G-Rk3 cream than in untreated mice. Further analysis proved that ginsenoside Rk3 could inhibit the decrease in water and hydroxyproline (HYP) levels in skin tissue and the loss of superoxide dismutase (SOD) and GSH-Px activities in blood. Moreover, ginsenoside Rk3 slowed or halted increases in malondialdehyde (MDA), matrix metalloproteinase 1 (MMP1) and MMP3 levels in the blood and interleukin 1 (IL-1), interleukin 6 (IL-6) and tumor necrosis factor α (TNF-α) in skin tissue. In conclusion, ginsenoside Rk3 plays a significant role in inhibiting photoaging and inflammation to protect skin health.